2019
DOI: 10.3390/ma12213593
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Shape Memory Alloy-Based Nanomechanical Resonators for Ultrathin Film Elastic Properties Determination and Heavy Mass Spectrometry

Abstract: Micro-/nanomechanical resonators are often used in material science to measure the elastic properties of ultrathin films or mass spectrometry to estimate the mass of various chemical and biological molecules. Measurements with these sensors utilize changes in the resonant frequency of the resonator exposed to an investigated quantity. Their sensitivities are, therefore, determined by the resonant frequency. The higher resonant frequency and, correspondingly, higher quality factor (Q-factor) yield higher sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Interestingly, recent studies have shown that NRs hold promise in the identification of even the larger masses (>GDa) (Dominguez-Medina et al, 2018;Stachiv and Gan., 2019;Stachiv et al, 2020;Erdogan et al, 2022). Moreover, there is a consensus among researchers that in order to gain more necessary information on the protein adsorption beyond its mass and position of attachment, a symbiosis of experiments with advanced theoretical modeling would be needed (Malvar et al, 2016;Stassi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, recent studies have shown that NRs hold promise in the identification of even the larger masses (>GDa) (Dominguez-Medina et al, 2018;Stachiv and Gan., 2019;Stachiv et al, 2020;Erdogan et al, 2022). Moreover, there is a consensus among researchers that in order to gain more necessary information on the protein adsorption beyond its mass and position of attachment, a symbiosis of experiments with advanced theoretical modeling would be needed (Malvar et al, 2016;Stassi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, there is an ongoing dispute on the application limits of the NRs, especially the multimode method, in the identification and analysis of a single or multiple protein(s) adsorbed on the resonator surface ( Tamayo et al, 2013 ). Interestingly, recent studies have shown that NRs hold promise in the identification of even the larger masses (>GDa) ( Dominguez-Medina et al, 2018 ; Stachiv and Gan., 2019 ; Stachiv et al, 2020 ; Erdogan et al, 2022 ). Moreover, there is a consensus among researchers that in order to gain more necessary information on the protein adsorption beyond its mass and position of attachment, a symbiosis of experiments with advanced theoretical modeling would be needed ( Malvar et al, 2016 ; Stassi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to their great potential and unique characteristics, microbeam resonant sensors have the advantages of small, fast, high sensitivity [4,5]. Besides, only a small amount of power is required to operate [6,7]. However, the structure nonlinearity and nonlinear electrostatic force seriously affect the performance of conventional micro-mass sensor [8][9][10].…”
Section: Introductionmentioning
confidence: 99%